If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(-6 + 4x) = 3x + -18 (-6 * -6 + 4x * -6) = 3x + -18 (36 + -24x) = 3x + -18 Reorder the terms: 36 + -24x = -18 + 3x Solving 36 + -24x = -18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 36 + -24x + -3x = -18 + 3x + -3x Combine like terms: -24x + -3x = -27x 36 + -27x = -18 + 3x + -3x Combine like terms: 3x + -3x = 0 36 + -27x = -18 + 0 36 + -27x = -18 Add '-36' to each side of the equation. 36 + -36 + -27x = -18 + -36 Combine like terms: 36 + -36 = 0 0 + -27x = -18 + -36 -27x = -18 + -36 Combine like terms: -18 + -36 = -54 -27x = -54 Divide each side by '-27'. x = 2 Simplifying x = 2
| 44428=974x+17156 | | 97=-7(x-7)-5x | | 2x^2-12x-34=0 | | 15x=9x+24 | | -6(4+6x)=-4x-24 | | 24x^2-40x-56=0 | | 52/7-5/14 | | 18-5x-2=-4 | | 7-(m-2)=12 | | 20Q+800=100+Q | | (2x-5)(3x^2-4x+1)=0 | | z^2+10z+11=0 | | 5(x+6)+1=3-2x | | 5(6m+7)=-2-7m | | s-9/10=21/10 | | 2(3w-12+w)=640 | | -9p=-72 | | 1.96x^5-4x^2-16x-16=0 | | 7-7(1-7x)=8x | | p(x)=-2x+100x-25 | | s-7/10=13/10 | | 12y=13.2 | | 5x+1+3=8(3x+2)+7(2-3x) | | 7(2y+1)=3(7+5y) | | X+x+.11+x+.11+.38=10.32 | | (2x+10)=(2x-15) | | 2(w+20+w)=380 | | -(1+6n)=-152 | | 121=0 | | 18-[2+3(8-5)]= | | 8(2+2x)-6=90 | | (x-2)2+(y+6)2=25 |